Effect of masonry infills on seismic performance of a 3 storey R - Lee, Han-Seon (Earthquake engineering & structural dynamics.)
The objective of this study is to investigate the effect of masonry infills on the seismic performance of low rise reinforced concrete (RC) frames with non-seismic detailing. For this purpose, a 2 bay 3 storey masonry infilled RC frame was selected and a 1 : 5 scale model was constructed according to the Korean practice of non-seismic detailing and the similitude law. Then, a series of earthquake simulation tests and a pushover test were performed on this model. When the results of these tests are compared with those in the case of the bare frame, it can be recognized that the masonry infills contribute to the large increase in the stiffness and strength of the global structure whereas they also accompany the increase of earthquake inertia forces. The failure mode of the masonry infilled frame was that of shear failure due to the bed joint sliding of the masonry infills while that of the bare frame appeared to be the soft storey plastic mechanism at the first storey. However, it is judged that the masonry infills can be beneficial to the seismic performance of the structure since the amount of the increase in strength appears to be greater than that in the induced earthquake inertia forces while the deformation capacity of the global structure remains almost the same regardless of the presence of the masonry infills.